Thyroid Dysfunction in Chronic Hepatitis C Patients Treated with Pegylated Interferon Alpha 2a and Ribavirin Combination Therapy and its Predisposing Factors - ANIQA ANSER, TASHIA MALIK, MUHAMMAD KHURRAM SALEEM, MUHAMMAD KASH (Journal of Fatima Jinnah Medical University, 2018)
Background: Pakistan carries one of the world’s highest burdens of the chronic hepatitis C and mortality due to liver failure. Chronic hepatitis C is treated with pegylated interferon alpha and ribavirin combination therapy. Changes in the thyroid function are common side effects of this antiviral treatment. Interferon alpha treatment can induce thyroid dysfunction in 2.5% to 20% of the treated patients. Study Design: Descriptive case series Methods: This study was conducted in Medical Unit II, Jinnah hospital Lahore from April 2013 to September 2013 and 220 chronic hepatitis C patients were included in this study. They were started on pegylated interferon and ribavin combination therapy for 6 months. Thyroid stimulating hormone (TSH) levels were measured at the start and after completion of this therapy. Factors leading to thyroid dysfunction including female gender, HCV genotype and smoking were also recorded in these patients. Results: Out of 220 patients enrolled in this study, 35 patients (15.91%) developed thyroid dysfunction in which 30 patients (13.64%) were hypothyroid while 5 patients (2.27%) were hyperthyroid. Out of these 35 patients, 23 patients (65.71%) were females. Conclusion: Thyroid dysfunction is a common side effect of interferon and ribavirin combination therapy. Only female gender was found to be a risk factor for the development of thyroid dysfunction.